Advances in Diagnostic Imaging of Hepatopulmonary Syndrome - Luo, Bi-Wei; Du, Zhi-Yong (Frontiers in Medicine, 2022)
Hepatopulmonary syndrome (HPS) is a serious pulmonary complication of progressive liver disease that leads to a poor clinical prognosis. Patients with HPS may develop acute respiratory failure, which requires intensive care and therapy. At present, the only effective treatment is liver transplantation; therefore, early diagnosis and timely treatment are of considerable significance. The three main features of HPS are liver disease, oxygenation disorder, and intrapulmonary vascular dilatation (IPVD). Diagnosing HPS is challenging due to the difficulty in detecting the presence or absence of IPVD. As such, imaging examination is very important for detecting IPVD. This paper reviews the imaging methods for diagnosing HPS such as ultrasound, dynamic pulmonary perfusion imaging, pulmonary angiography, and computed tomography.